The Use of Loose Parts in Enhancing the Naturalist Intelligence of Early Childhood - Uyu Muawanah; Eva Yulianingsih; Rani Puspita Sari (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study aims to determine how educators can use learning materials that include loose components with students in the 4-5 and 5-6 year-old ranges in RA Al-Muhajirin Tangerang Regency. Meanwhile, the study seeks to determine whether using these materials improves students' creative and imaginative thinking capacity. At Tangerang Regency's RA Al-Muhajirin, instruction is based on loose pieces. RA Al-Muhajirin in Tangerang Regency conducted this study during the academic year 2022–2023. This study employs a qualitative research design. Where a description describes the research's findings. Techniques for gathering data include documentation, observation, and interviews. The study's findings demonstrate that RA Al-Muhajirin educators have employed Loase Parts as teaching tools.